Penerapan Cabri II Plus Untuk Meningkatkan Kemampuan Pemahaman Matematis dan Motivasi Belajar Siswa dalam Pembelajaran Matematika - Rezkiyana Hikmah; Purni Munah Hartuti (SAP (Susunan Artikel Pendidikan), 2018)
This research aims to study the improvement of mathematical understanding ability of students studying with cabri II plus and students studying with traditional learning and to examine the learning motivation of students studying with cabri II plus. The research uses a quasi-experimental research design with non-equivalent control groups formed using purposive sampling technique. The research population is seventh grade students of Cibinong Junior High School with 30 students in the experimental and control classes. The instruments used are a pretest and posttest on students' mathematical comprehension ability and a questionnaire on learning motivation for the experimental class students. Data are analyzed using Mann-Whitney U test and t test. The results show that the increase in the of mathematical understanding ability of students studying with cabry II plus is no better than students studying with traditional learning. The learning motivation of students studying with Chili II plus software in general belongs to a medium motivation category